Practice Level and Associated Factors Towards the Preventive Measures of COVID-19 Among the General Population; A Systematic Review and Meta-Analysis - Tadesse, Abay Woday; Aychiluhm, Setognal Birara; Mare, Kusse Urmale; Tarekegn, Setegn Mihret; Biset, Gebeyaw (Frontiers in Public Health, 2022)
Abstract Background: Globally, countries have taken scientifically proven preventive measures to halt the spread of COVID-19. However, studies conducted on the practice of these preventive methods across the world are highly inconsistent and inconclusive. Hence, this study intended to estimate the pooled COVID-19 preventive practice and its determinants among the general population. Methods: This study was conducted using online databases (PubMed, HINARI, Scopus, EMBASE, Science Direct, and Cochrane library database), African Journals online, Google Scholar, open grey and online repository accessed studies. The quality of the included studies was assessed using Newcastle-Ottawa Quality Assessment Scale (NOS). We have employed STATA 14.0 software for analysis. The existence of heterogeneity between studies was checked using Cochran Q test and I2 test statistics and then, the presence of publication bias was detected using both funnel plot and Egger’s test. The pooled level of preventive practice towards COVID-19 and the odds ratio (OR) with a 95% confidence interval was presented using forest plots. Results: In this review, 51 studies were included and the pooled level of practice towards the preventive measures of COVID-19 was 74.4% (95% CI: 70.2%– 78.6%, I2 = 99.7%, P<0.001] using a random effects model. Being female [OR=1.97: 95% CI 1.75, 2.23; I2 =0.0%, P<0.698], residing in rural areas [OR=0.53: 95% CI 0.44, 0.65; I2 =73.5%, P<0.013], attending higher education level [OR=1.47: 95% CI 1.18, 1.83; I2 =75.4%, P<0.001], being employed [OR=2.12: 95% CI 1.44, 3.12; I2 =91.8%, P<0.001], being age < 30 [OR=0.73: 95% CI 0.60, 0.89; I2 =73.9%, P<0.001], and having knowledge above median score [OR=1.22: 95% CI 1.09, 1.36; I2 =47.3%, P <0.077] were the independent predictors of adequate practice level towards the preventive measures of COVID-19. Conclusions: The study revealed that nearly three-fourths of the general population has an adequate level of practice on the preventive measures of COVID-19. Thus, the global, regional, national, and local governments need to establish policies and strategies that encourage people to adhere the recommended preventive measures and priority should be given to address the identified factors.